2001
DOI: 10.1002/1522-2683(200107)22:12<2398::aid-elps2398>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Separation of peptides utilizing ultrahigh-temperature micellar electrokinetic chromatography

Abstract: The use of ultrahigh column temperatures, up to 110 degrees C, in micellar electrokinetic capillary chromatography was investigated. The number of plates generated per unit time increased from 0.22 to 12.8 plates/s for separations at 15 degrees C and 110 degrees C, respectively. Ultrahigh-temperature micellar electrokinetic capillary chromatography was used for the separation of cyclic undecapeptides (cyclosporins). A minimum resolution of 1.39 was calculated for a critical peak pair at 110 degrees C, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Relatively few applications have been found using MECC for protein separation. MECC is well suited for separation of peptides that have similar structures and electrophoretic mobilities (24,25). Depending on the electrostatic and hydrophobic interactions of analyte and surfactant, anionic, cationic, and zwitterionic surfactants can be chosen to optimize the resolution of peptides (24).…”
Section: Micellar Electrokinetic Capillarymentioning
confidence: 99%
“…Relatively few applications have been found using MECC for protein separation. MECC is well suited for separation of peptides that have similar structures and electrophoretic mobilities (24,25). Depending on the electrostatic and hydrophobic interactions of analyte and surfactant, anionic, cationic, and zwitterionic surfactants can be chosen to optimize the resolution of peptides (24).…”
Section: Micellar Electrokinetic Capillarymentioning
confidence: 99%
“…Most papers on MEEKC have reported that the concentration of surfactant, buffer pH, column temperature, and the type of organic modifier all have dominating effects on the separation and selectivity for this system [6,7]. Similarly, the above four factors are also utilized to improve MEKC separations [14,15]. Hence, the influence of surfactant, buffer pH, temperature, and organic modifier for benzophenone separation by MEEKC and MEKC methods were compared in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Two effects determine the separation results of both MEEKC and MEKC systems. One is the difference of the partition coefficients of analytes in pseudostationary and aqueous phases (chromatographic effect), and the other one is the difference of migration velocities of analytes in electric fields (electrophoresis effect) [11][12][13][14][15]. Unlike the micelle that is regarded as pseudostationary phase for MEKC, the surfactant-coated oil droplets in microemulsion are employed as the pseudostationary phase for MEEKC.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of SDS=TM-bCD, similarly to what observed using DM-bCD, could promote the formation of SDS aggregates characterized by a lower partitioning ability toward the solutes (Mileo et al 2008;Bendazzoli et al 2010). This mixed pseudostationary phase resulted to be effective in analysis of the closely related hydrophobic cyclosporins allowing their separation without the needs for high (and ultra-high) temperature (Djordjevic et al 2001). …”
Section: Cd-mekc Analysis Of Cyclosporins 671mentioning
confidence: 99%
“…Djordjevic et al (2001) achieved the MEKC separation of cyclosporins congeners, namely, CyA, B, C, D, and G in conditions of ultrahigh temperature (110 C) and the analysis time was long (96 min). The reported methods were applied to the determination of CyA in pharmaceuticals; however, the potential in separation of degradation impurities was not considered.…”
mentioning
confidence: 99%